PELATIHAN PENYUSUNAN PERANGKAT PEMBELAJARAN DENGAN PENDEKATAN DEEP LEARNING BAGI GURU-GURU SMAK SANTIO GERARDUS MAYELLA KALEMBUWERI - Agustinus Tanggu Daga; Kristoforus Tanggela (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
The main issue at Santo Gerardus Mayella High School is that teachers have not yet acquired the capability to develop deep learning instructional modules. The objective of this training is to facilitate teachers in enhancing their skills in creating deep learning instructional modules. The training was conducted as an In-House Training using methods such as seminars, collaborative practice, and presentations. The program lasted for three days following a schedule agreed upon with the Principal. The training outcomes demonstrated significant improvements among participants, both in their understanding of the Independent Curriculum and deep learning, as well as in their skills to develop deep learning instructional modules. These achievements were supported by professional resource persons, relevant materials, appropriate training methods, and adequate facilities. Participants’ perceptions also indicated that the training was highly beneficial in improving their module development skills and motivated them to implement the training results in classroom teaching.